Pengaruh Dukungan Teman Sebaya terhadap Adaptabilitas Karier Siswa melalui Self-Efficacy - Nadia Amillatur Risqi; Edwindha Prafitra Nugraheni (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Career adaptability is a crucial psychosocial resource that enables students to cope with career developmental tasks, educational transitions, and unpredictable challenges. Peer support is considered an important social factor that can enhance students’ self-efficacy, which in turn contributes to career adaptability. This study aims to examine the effect pf peer support on career adaptability through self-efficacy among senior high school students in Semarang. This study employed a quantitative approach with a correlational design involving 227 students selected using proportional random sampling. Data were collected using the Peer Support Scale, General Self-Efficacy Scale, and Career Adapt-Abilities Scale-Short Form. Mediation analysis was conducted using a regression-based approach. The results showed that peer support had a significant positive effect on career adaptability  (β = 0.214; p < 0.001). Self-efficacy also significantly predicted career adaptability (β = 0.050; p < 0.05) and partially mediated the relationship between peer support and career adaptability (indirect effect = 0.010; p < 0.001). These findings provide empirical support for the role of self-efficacy as a psychological mechanism linking social support and career adaptability. Practically, the results highlight the importance of peer-based interventions and self-efficacy enhancement within school guidance and counseling programs to support students’ career development.